POSE YOGA DALAM KARYA KRIYA - Didiek Prasetya (UNIVERSITAS INDO GLOBAL MANDIRI, 2016)
Yoga is a way to achieve harmony and balance the mind. In the program Seven Spiritual Laws of Yoga aims to achieve success is a natural law that is applied to the human exsperiece. Yoga is a series of principles that create what has not materialized be realized. Yoga poses made in the depiction of human life, therefore in the process of creating works of yoga poses are in though as the source of the idea of creation into a work of art. Source of inspiration in this work is a yoga pose from The Seven Spiritual Laws of Yoga. The findings in this creation is the incorporation of wood circles 2cm diameter and 2.3 cm in the work of art.